Development of the user friendly spreadsheet based SPC (statistical process control) on SME company - Mohd Yusri, Yusof (2007)
This Final Year Project is about the development of the user friendly spreadsheet based on SME company. Spreadsheet is a database that used to store or managed large data in order to have a good management in data collection. Besides that, spreadsheet itself is very useful in viewing the performance of the production process on certain company. This is because the spreadsheet that need to develop will applied SPC (statistical process control) which provide graphical tools and method on how to analyze a set of data. The objective of this project is to perform a set of graph base on the data collection that has been collected from the product produce by SME company. This project also has an alternative method on analyzing the set of data that have been collected. First one is about hypothesis testing which is a decision making analysis on the production performance on that day. With this hypothesis testing, the claim will be determined whether it will be rejected or acceptable by referring to the distribution graph provided. Second one is about confidence interval. It will guide the user to know the estimation of weight of cake produced on that day. So, by developing this project, it will make sure the SUE company can have a good management besides having a good performance on production process.